ANALISIS PENGANGGARAN MODAL PADA PT ULTRAJAYA MILK INDUSTRY Tbk. TAHUN 2013-2017 - Wulandari, Eka Lusvita; Harahap, Lily Rahmawati (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2018)
Capital budgeting in practice is intended to conduct an investment analysis of some available investment alternatives, and then determine or choose the most profitable investment. Inappropriateness in determining investment options will result in losses of either real losses or losses due to loss of opportunity to gain an opportunity cost that can actually be realized. The investment analysis will select the available investment opportunities, so that investment can be selected that will provide the greatest benefit of every dollar invested. Capital budgeting techniques can be analyzed by appraisal method of investment as follows: Average Rate of Return, Payback Period , Net Present Value, and Profitability Index.